Contractul inteligent un capitol nou în dreptul obligațional - Cara-Rusnac, Aliona (CEP USM, 2024)
This article aims to research the main issues of the smart contracts as a new era in the law of obligations. The smart contract has the capacity to disrupt the practice of the traditional contracting. The fundamental scope of the article is to analyze whether these are contracts in the legal sense and to describe their benefits and potential threats. The paper will outline two main directions, first that smart contracts are well managed by some classic principles of formation of the contract but in the same time there are some key particular issues associated with technology that makes a new brand contract in the obligational right domain.
SMART CONTRACT A NEW CHAPTER IN LAW OF OBLIGATIONS
Keywords: contract inteligent; smart; blockchain; bitcoin; inovație; descentralizat; auto-executoriu